Relationship Between Parental Marital Conflict and Social Anxiety Symptoms of Chinese College Students: Mediation Effect of Attachment - Adare, Aklilu A.; Zhang, Yuewen; Hu, Yaqi; Wang, Zhenhong (Frontiers in Psychology, 2021)
Social anxiety has been a common problem among college students and has an adverse impact on their adaptation outcomes. Among influential factors, parental marital conflict and attachment (parental and peer attachment) have been found to be related to college students’ social anxiety symptoms, however, little is known how parental marital conflict and attachment jointly contribute to college students’ social anxiety symptoms. The current study explored this issue. Self-reported questionnaire of Children’s Perception of Inter-parental Conflict Scale (CPIC), Inventory of Parent and Peer Attachment (IPPA), and the Social Interaction Anxiety Scale (SIAS) were administered to 707 undergraduate students (Mean age = 19.27, SD = 0.97). Results indicated that perceived parental marital conflict was positively correlated with social anxiety symptoms and was negatively associated with parental and peer attachment. Parental and peer attachment were negatively correlated with social anxiety symptoms. Mediation analyses indicated that perceived parental marital conflict exerted its indirect effect on social anxiety symptoms through a serial multiple mediation role of parental and peer attachment. The present findings highlight the serial multiple mediation role of parental and peer attachment in the relationship between perceived parental marital conflict and college students’ social anxiety symptoms.